THE EFFECT OF TRAIN NUMBER GAME TOWARD THE SUMMATION ARITHMATIC ABILITY FOR STUDENT WITH INTELLECTUAL DISABILITY - Anita Rachmawati; Umi Safiul Ummah (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purpose of this research was to describe the effect of train number game toward the summation arithmetic ability for student with intellectual disability of the second grade in SDLB Eka Mandiri Kota Batu. Data collecting from students was tests and observation. Data analysis in this study used descriptive statistics analysis of visual graphs on analysis in and intercondition. The results indicated that the train number game contributing in both increasing and effecting of 1-10 summation arithmetic ability for student with intellectual disability.